The Influence of Project-Based Learning Model to Improve Students’ Creative Thinking on Colloid Subject - Isbullah, Isbullah; Supardi, Kasmadi Imam; Jumaeri, Jumaeri (Journal of Innovative Science Education, 2019)
Creative thinking skill plays important roles in developing student?s creativity in solving problems. This study aims at investigating the influence of project-based learning model in improving students? creative thinking on colloid subject. This study used experimental one group (pretest-posttest) design. 38 students were involved in this study as the samples. According to the analysis results, the N-gain score of the students? creative thinking skill was 0.72 (high). The analysis showed that project-based learning model gave significant improvement, and the students showed very good response to project-based learning model. Therefore, the model is recommended to be applied in schools.